Randomized trial of a home monitoring system for early detection of choroidal neovascularization home monitoring of the Eye (HOME) study - Chew, Emily Y; Clemons, Traci E; Bressler, Susan B; Elman, Michael J; Danis, Ronald P; Domalpally, Amitha; Heier, Jeffrey S; Kim, Judy E; Garfinkel, Richard (Ophthalmology (Rochester, Minn.), 2014)
To determine whether home monitoring with the ForeseeHome device (Notal Vision Ltd, Tel Aviv, Israel), using macular visual field testing with hyperacuity techniques and telemonitoring, results in earlier detection of age-related macular degeneration-associated choroidal neovascularization (CNV), reflected in better visual acuity, when compared with standard care. The main predictor of treatment outcome from anti-vascular endothelial growth factor (VEGF) agents is the visual acuity at the time of CNV treatment. Unmasked, controlled, randomized clinical trial. One thousand nine hundred and seventy participants 53 to 90 years of age at high risk of CNV developing were screened. Of these, 1520 participants with a mean age of 72.5 years were enrolled in the Home Monitoring of the Eye study at 44 Age-Related Eye Disease Study 2 clinical centers. In the standard care and device arms arm, investigator-specific instructions were provided for self-monitoring vision at home followed by report of new symptoms to the clinic. In the device arm, the device was provided with recommendations for daily testing. The device monitoring center received test results and reported changes to the clinical centers, which contacted participants for examination. The main outcome measure was the difference in best-corrected visual acuity scores between baseline and detection of CNV. The event was determined by investigators based on clinical examination, color fundus photography, fluorescein angiography, and optical coherence tomography findings. Masked graders at a central reading center evaluated the images using standardized protocols. Seven hundred sixty-three participants were randomized to device monitoring and 757 participants were randomized to standard care and were followed up for a mean of 1.4 years between July 2010 and April 2013. At the prespecified interim analysis, 82 participants progressed to CNV, 51 in the device arm and 31 in the standard care arm. The primary analysis achieved statistical significance, with the participants in the device arm demonstrating a smaller decline in visual acuity with fewer letters lost from baseline to CNV detection (median, -4 letters; interquartile range [IQR], -11.0 to -1.0 letters) compared with standard care (median, -9 letters; IQR, -14.0 to -4.0 letters; P = 0.021), resulting in better visual acuity at CNV detection in the device arm. The Data and Safety Monitoring Committee recommended early study termination for efficacy. Persons at high risk for CNV developing benefit from the home monitoring strategy for earlier detection of CNV development, which increases the likelihood of better visual acuity results after intravitreal anti-VEGF therapy.